More training, less security? Training and the quality of life at work in Argentina, Brazil and Chile. - Jeria Cáceres, Maria Mercedes (International Labour Review, 2002)
In order to assess the effect of vocational training, the author explores the findings of People's Security Surveys conducted in Argentina, Brazil and Chile; she uses conditional multiple correspondence analysis (a descriptive statistical method). She observes that training tends to be a consequence, rather than a cause of promotion. Though for the worker, training does result in increased work outcomes or advantages (earnings levels, work-related benefits), it also results in greater work costs or inputs (in terms of variable income, hours of work and work-related insecurity). Reprinted by permission of the publisher.